Inheritance of morphological characters and sex expression in castor (Ricinus communis L.): INHERITANCE OF MORPHOLOGICAL CHARACTERS AND SEX EXPRESSION IN CASTOR - M RAMESH; C LAVANYA; M SUJATHA; M H V BHAVE; J ARUNA KUMARI (Journal of Oilseeds Research, 2017)
The segregation of morphological characters and sex expression of the traits was studied to understand the pattern of inheritance involving pistillate lines from different backgrounds like S type, NES and new sources like using F1 and F2 populations. Inheritance of stem colour in four crosses of pistillate x monoecious lines indicated that stem colour was controlled by single gene while red stem colour was dominant over green stem colour in F1. However, in other cross it showed digenic epistatic ratio. Study on bloom colour indicates that it is controlled by monogene and presence of bloom was dominant over absence of bloom respectively. While the present study indicated that two genes control the leaf shape in three crosses where as in presence of either of a dominant gene masks the phenotype as flat or semi-cup while both recessive genes result in cup shaped leaf. Sex expression character indicating the dominance of monoecious over pistillate character in some crosses while in other crosses the dominance of pistillate character over the monoecious character. Based on sex expression study it concluded that the proportion of monoecious and pistillate flowers is greatly influenced by both genetic and non-genetic factors.